(untitled) (GEON Journal (Management, Organizations and Business), 2014)
This article’s main objective is to offer a synthesis of the study that would make the author on dropout and repetition in the Business Administration program at the University of the Llanos during the period between 2008 and 2012, as well as its proposal to address these phenomena and improve retention rates and academic performance of students in the program. To accomplish that task has been divided writing into two parts: The first part presents, in summary, the conceptual framework and methodology used in the study; in the second a summary of the diagnosis of dropout and repetition in the selected academic period is presented.